Emotional intelligence and stock trading decisions: Indonesia’s millennial generation in the COVID-19 era - Sutejo, Bertha Silvia; Sumiati; Wijayanti, Risna; Ananda, Candra Fajri (Asian Economic and Financial Review, 2023)
This study explores the relationship between emotional intelligence traits and stock trading choices made by young millennial (Generation Y) investors in Indonesia, particularly during the COVID-19 pandemic. It also investigates whether behavioral biases, such as overconfidence and the herding effect, can mediate this relationship. This study uses exogenous variables (emotional intelligence trait), endogenous variables (stock trading decisions), and mediating variables (overconfidence and herding effect) to conduct fundamental research. A sample of 500 young investors in Indonesia from the millennial age was given a questionnaire with 5-point Likert scale response options. A Sobel calculator is used for mediation testing, and a structural equation model (SEM) is used for hypothesis testing. The study's conclusions show that there is no connection between emotional intelligence and stock trading choices. The findings also indicate that, in contrast to the herding effect, overconfidence has a significantly favorable impact on stock trading judgments. Tests of mediation reveal that the overconfidence behavior bias mediates the link between the emotional quotient and stock trading choices to some extent. The association between emotional intelligence and stock trading decisions was found to be independent of the herding effect. Young millennial investors can deliberately reduce the impact of these biases on their decision-making process, improve their self-awareness, and make more logical decisions. This could result in more knowledgeable and successful investment plans during difficult times, such as the COVID-19 pandemic.